Improving BandWidth Utilization in Software Defined Networks (SDN) - احمد, أحمد; محمد, عفراء (Latakia University Journal -Engineering Sciences Series, 2020)
Software Defined Networks (SDN) is the qualitative movement in the field of networks due to that fact that it separates the control elements from the routing elements, and the function of the routing elements was limited to the implementation of the decisions that are sent to it by the controller through the OpenFlow Protocol (OF) which is mainly used in SDN. We explain in this paper the benefit of the new concept which is presented by SDN and it makes network management easier, so instead of writing the rules on each device, we program the application in the controller, and the infrastructure devices run the received commands from the controller. In order to achieve the best performance of this technology, a Quality of Service (QoS) must be applied within it, where it includes several criteria, the most important are the used bandwidth, delay, packet loss and jitter. The most important of these criteria is the bandwidth, because by improving this standard, we can improve the rest of the other criteria. Therefore, in this paper, we provide the necessary improvement on the RYU controller to use the best bandwidth, which improves the quality of service in SDN.